MODAL SOSIAL PADA USAHA RUBIK GANEPO DI JORONG PADANG KANDI NAGARI VII KOTO TALAGO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Novera Fitri Yanti; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Rubik ganepo is a snack food whose basic ingredients are made from cassava whichwill be cut in dice thrn processed into yellow crackers derived from turmeric. Thisone food has long since its existence but its existence still survive until now. One ofwhich is in the area Jorong Padang Kandi Nagari VII Koto Talago which is theproduction center of rubik ganepo business. The purpose of this research is to knowthe elements of social capital in rubik ganepo business as well as social capitalbenefits in rubik ganepo business. This research uses qualitative approach withdescriptive analysis. Selection of informants in this study was conducted by purposivesampling technique that is taking data informants based on certain criteria. Thesecriteria are entrepreneurs who are members of the senior ganepo group in which theprocess of production and marketing is wide. Techniques used in this study areinterviews, observation, documentation. The results of this study indicate that theelements of social capital in rubik ganepo business consist of networks, trust, andnorms. The benefits of social capital in the from of a network is easier in marketingthe rubik ganepo business, make it easier to get of raw materials, improving goodrelations between actors. The benefits of trust capital such as transactions becomesmooth, goods or supply of raw materials as desired, proce negotitation goes well.The benefits of norms such as farmers are being cautious in the acquisition of rawmaterials, the quality rubik ganepo guaranteed, competition between entrepreneur ishealthy.Keyword: Social Capital, Rubik ganepo busines